2014 IEEE International Conference on Robotics and Automation (ICRA) 2014
DOI: 10.1109/icra.2014.6907567
|View full text |Cite
|
Sign up to set email alerts
|

A reduced-gravity simulator for physically simulating human walking in microgravity or reduced-gravity environment

Abstract: Astronauts must go through extensive training of their tasks in a simulated microgravity or reduced-gravity environment before they can perform the same tasks in space. Scientists and engineers also need simulated reduced-gravity facilities to study human performance and factors in space. This paper presents a novel design and prototype test of a multi-DOF reduced-gravity simulator which can be used for training astronauts and studying human factors in zero or partial gravity environment. Designed based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In this study, we found that the effect of lower-body positive-pressure treadmill (LBPPT) walking, specifically an increase in body weight support, or a reduction in gravity from 100% (normal gravity) to 40% and 20% (reduced gravity) body weight (BW), is mainly characterized by a significant decrease in center of pressure (COP) anterior–posterior segment length and simultaneous significant increase in COP medial–lateral segment width. The calculated COP location and its movement during the stance phase of each cycle are typically reported as indicators of marked gait stability during dynamic tasks such as walking [ 20 , 21 ]. This alteration in gait stability may be suggestive of a shift in walking patterns as gravity conditions are reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that the effect of lower-body positive-pressure treadmill (LBPPT) walking, specifically an increase in body weight support, or a reduction in gravity from 100% (normal gravity) to 40% and 20% (reduced gravity) body weight (BW), is mainly characterized by a significant decrease in center of pressure (COP) anterior–posterior segment length and simultaneous significant increase in COP medial–lateral segment width. The calculated COP location and its movement during the stance phase of each cycle are typically reported as indicators of marked gait stability during dynamic tasks such as walking [ 20 , 21 ]. This alteration in gait stability may be suggestive of a shift in walking patterns as gravity conditions are reduced.…”
Section: Discussionmentioning
confidence: 99%
“…COP, when examining kinetic plantar pressure measures, is typically used to identify and assess any issues with an individual’s foot pathology during gait. The calculated COP location and its movement during the stance phase of each cycle is reported as an indicator of marked gait stability during dynamic tasks such as walking [ 20 , 21 ]. It was suggested that the assessment of plantar pressure could be an appropriate substitute for measuring foot trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while very relevant to space exploration (29)(30)(31)(32)(33), completely immersing participants in a novel gravity field is not representative of other applications. For instance, it is common to use devices to support a patient's limb and reduce their muscle effort required to counteract gravity in rehabilitation (34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in parabolic flights have allowed to test this theory in a couple of hypo- and hyper-gravity fields with a limited number of trials and participants ( 5, 9, 12, 13 ). Moreover, while very relevant to space exploration ( 2933 ), completely immersing participants in a novel gravity field is not representative of other applications. For instance, it is common to use devices to support a patient’s limb and reduce their muscle effort required to counteract gravity in rehabilitation ( 3442 ).…”
Section: Introductionmentioning
confidence: 99%
“…For this configuration to function properly, the elastic element and the link between the elastic element and the motor need to be carefully selected and designed to result in an appropriate equilibrium position and torque profile [165]. They have been used for gravity compensation [166,167], in exoskeletons to reduce motor torque and power requirements during load lifting [168], and for efficient locomotion with large payloads [169].…”
Section: Parallel Elastic Actuatorsmentioning
confidence: 99%